Dihydroxyacetone metabolism in Haloferax volcanii - Ouellette, Matthew; Makkay, Andrea M.; Papke, R Thane (Frontiers in Microbiology, 2013)
Dihydroxyacetone (DHA) is a ketose sugar that can be produced by oxidizing glycerol. DHA in the environment is taken up and phosphorylated to DHA-phosphate by glycerol kinase or DHA kinase. In hypersaline environments, it is hypothesized that DHA is produced as an overflow product from glycerol utilization by organisms such as Salinibacter ruber. Previous research has demonstrated that the halobacterial species Haloquadratum walsbyi can use DHA as a carbon source, and putative DHA kinase genes were hypothesized to be involved in this process. However, DHA metabolism has not been demonstrated in other halobacterial species, and the role of the DHA kinase genes was not confirmed. In this study, we examined the metabolism of DHA in Haloferax volcanii because putative DHA kinase genes were annotated in its genome, and it has an established genetic system to assay growth of mutant knockouts. Experiments in which Hfx. volcanii was grown on DHA as the sole carbon source demonstrated growth, and that it is concentration dependent. Three annotated DHA kinase genes (HVO_1544, HVO_1545, and HVO_1546), which are homologous to the putative DHA kinase genes present in Hqm. walsbyi, as well as the glycerol kinase gene (HVO_1541), were deleted to examine the effect of these genes on the growth of Hfx. volcanii on DHA. Experiments demonstrated that the DHA kinase deletion mutant exhibited diminished, but not absence of growth on DHA compared to the parent strain. Deletion of the glycerol kinase gene also reduced growth on DHA, and did so more than deletion of the DHA kinase. The results indicate that Hfx. volcanii can metabolize DHA and that DHA kinase plays a role in this metabolism. However, the glycerol kinase appears to be the primary enzyme involved in this process. BLASTp analyses demonstrate that the DHA kinase genes are patchily distributed among the Halobacteria, whereas the glycerol kinase gene is widely distributed, suggesting a widespread capability for DHA metabolism.